Diagnosis of inherited platelet disorders on a blood smear: a tool to facilitate worldwide diagnosis of platelet disorders. (4th June 2017) - Greinacher, A.; Pecci, A.; Kunishima, S.; Althaus, K.; Nurden, P.; Balduini, C. L.; Bakchoul, T.
Abstract : Essentials There are many hereditary platelet disorders (HPD) but diagnosing these is challenging. We provide a method to diagnose several HPDs using standard blood smears requiring < 100 µL blood. By this approach, the underlying cause of HPD was characterized in ~25–30% of referred individuals. The method facilitates diagnosis of HPD for patients of all ages around the world. Summary: Background: Many hereditary thrombocytopenias and/or platelet function disorders have been identified, but diagnosis of these conditions remains challenging. Diagnostic laboratory techniques are available only in a few specialized centers and, using fresh blood, often require the patient to travel long distances. For the same reasons, patients living in developing countries usually have limited access to diagnosis. Further, the required amount of blood is often prohibitive for pediatric patients. Objectives: By a collaborative international approach of four centers, we aimed to overcome these limitations by developing a method using blood smears prepared from less than 100 μL blood, for a systematic diagnostic approach to characterize the platelet phenotype. Methods: We applied immunofluorescence labelling (performed centrally) to standard air‐dried peripheral blood smears (prepared locally, shipped by regular mail), using antibodies specific for proteins known to be affected in specific hereditary platelet disorders. Results: By immunofluorescence labelling of blood smears we characterized the underlying cause in 877/3217 (27%) patients with suspected hereditary platelet disorders (HPD). Currently about 50 genetic causes for HPD are identified. Among those, the blood smear method was especially helpful to identify MYH9 disorders/ MYH9 ‐related disease, biallelic Bernard‐Soulier syndrome, Glanzmann thrombasthenia and gray platelet syndrome. Diagnosis could be established for GATA1 macrothrombocytopenia, GFI1B macrothrombocytopenia, ß1‐tubulin macrothrombocytopenia, filamin A‐related thrombocytopenia and Wiskott‐Aldrich syndrome. Conclusion: Combining basic and widely available preanalytical methods with the immunomorphological techniques presented here, allows detailed characterization of the platelet phenotype. This supports genetic testing and facilitates diagnosis of hereditary platelet disorders for patients of all ages around the world.